2001
DOI: 10.1056/nejm200102013440501
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations and the Risk of Relapse in Multiple Sclerosis

Abstract: Vaccination does not appear to increase the short-term risk of relapse in multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
0
19

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(195 citation statements)
references
References 36 publications
5
171
0
19
Order By: Relevance
“…24,28 However, these were underpowered to demonstrate rare events, nor did they document less serious events that may have prompted outpatient physician visits. Randomized controlled trials and observational studies in multiple sclerosis 29,30 and rheumatoid arthritis 31 also did not demonstrate increased risk of disease flare after immunization. The primary advantage of the current study is its large numbers of included children with IBD and its ability to assess the full spectrum of health system utilization.…”
Section: Figurementioning
confidence: 91%
“…24,28 However, these were underpowered to demonstrate rare events, nor did they document less serious events that may have prompted outpatient physician visits. Randomized controlled trials and observational studies in multiple sclerosis 29,30 and rheumatoid arthritis 31 also did not demonstrate increased risk of disease flare after immunization. The primary advantage of the current study is its large numbers of included children with IBD and its ability to assess the full spectrum of health system utilization.…”
Section: Figurementioning
confidence: 91%
“…About 200 cases of CNS demyelinating disorders within 2 months after HBV vaccination were reported to the French pharmacovigilance system [72] and 2 years later, the French government suspended routine immunization of preadolescents in schools [73]. However, these studies were criticized for methodological limitations, including methods used for case ascertainment and control selection, the validation of vaccination status, and limited statistical power, since the findings of two large-scale studies have shown no significant association between HBV vaccination and the MS occurrence [74,75], but different opinions have also been formulated. For instance, an unpublished study showed by the Bcapture-recapture^method that the real number of MS cases linked to HBV vaccine was 2-2.5 higher than the officially registered number in the French pharmacology.…”
Section: Hbv Vaccine and Multiple Sclerosismentioning
confidence: 99%
“…For example, a provider may believe that a given vaccination was likely responsible for a temporally related exacerbation of multiple sclerosis (MS), but input from neurologic consultants could reassure the practitioner that MS exacerbations are common and that multiple studies have not supported their increased risk after vaccination [48]. Also, panel experts can clarify the most likely diagnosis, such as the fixed-drug reaction to aluminum in Case 2 and provide appropriate recommendations regarding future immunization options.…”
Section: Discussionmentioning
confidence: 99%